Science, mythe et poésie dans le « Catalogue des serpents » de Lucain (Phars. IX, 700-733) - Sébastien Barbara (Pallas, 2009)
This study analyses the principles retained by Lucan in organising his list of ophidians and thus deciphers the ≪ catalogal ≫ writing of the poet in the light of his poetic and scientific choices. There results from an examination of those data that Lucan accords a great importance to the iological and legendary approaches for reasons at once aesthetic and symbolic and that the pride of place reserved to the name and etymology is significant of an essentially poetic approach of the world. For Lucan, torn between a limited science and a fine but inaccurate aition, poetry is a third way to express the world and its beauties that allows all manner of licences.